Carica papaya induces in vitro thrombopoietic cytokines secretion by mesenchymal stem cells and haematopoietic cells - Aziz, J.; Abu Kassim, N.L.; Abu Kasim, N.H.; Haque, N.; Rahman, M.R. (BioMed Central, 2015)
Background: Use of Carica papaya leaf extracts, reported to improve thrombocyte counts in dengue patients, demands further analysis on the underlying mechanism of its thrombopoietic cytokines induction. Methods: In vitro cultures of peripheral blood leukocytes (PBL) and stem cells from human exfoliated deciduous teeth (SHED) were treated with unripe papaya pulp juice (UPJ) to evaluate its potential to induce thrombopoietic cytokines (IL-6 and SCF). Results: In vitro scratch gap closure was significantly faster (p < .05) in SHED culture treated with UPJ. IL-6 concentration was significantly increased (p < .05) in SHED and PBL culture supernatant when treated with UPJ. SCF synthesis in SHED culture was also significantly increased (p < .05) when treated with UPJ. Conclusion: In vitro upregulated synthesis of IL-6 and SCF both in PBL and SHED reveals the potential mechanism of unripe papaya to induce thrombopoietic cytokines synthesis in cells of hematopoietic and mesenchymal origin.